Analysis of the Implementation of Differentiated Learning in the Implementation of the Independent Curriculum in Middle School Mathematics Lessons - Rina Febriana; Sugiman Sugiman; Ariyadi Wijaya (CV. AFDIFAL MAJU BERKAH, 2023)
Differentiated learning is a form of addressing the diverse learning needs of students paying close attention to readiness, learning profiles, interests, and aptitudes. This study aims to find out (1) the planning stage (plan) carried out by the mathematics teacher in implementing differentiation learning, (2) the (do) stage, the differentiation learning process applied in class, (3) the (see) stage, the form of assessment (evaluation). ) carried out by the teacher in the implementation of learning. The research method used is qualitative by collecting data through observation (learning videos) and interviews. The results of the research are that at the planning stage, the teacher does it by preparing everything that supports differentiation learning; at the do stage,e the teacher implements the learning that has been designed at the planning stage and the seeseedage, the teacher evaluates the learning process that has been carried out at the see stage both in terms of using the learning method as well as in terms of student understanding which is carried out to improve the learning stage in the future. In differentiation learning, this is adapted to the school's circumstances and the student’s abilities; one school may be different from another but has the same goal, and in differentiation learning, It must contain 3, namely differentiation of content, process, and product.